Towards a Kachru Institute. Issue 1 (9th July 2019) - Crystal, David
Abstract: In September 1984, Braj Kachru suggested that an institutional archive for research on the English language across cultures should be set up. In Kachru's view, this project would include six strands of activity, including empirical sociolinguistic studies, pedagogical studies, resource materials, special registers, functional domains and formal studies. Over the succeeding decades, however, no such institute came into existence. This current paper therefore seeks to revive the plan to create such an institute, which, of course, should be appropriately named as 'The Kachru Institute'.